2008
DOI: 10.1103/physreve.78.045303
|View full text |Cite
|
Sign up to set email alerts
|

Theory for particle settling and shear-induced migration in thin-film liquid flow

Abstract: Particles suspended in a film flow can either settle out of the flow, remain well mixed, or even advance faster than the fluid, accumulating at the moving contact line. Recent experiments by Zhou et al. [Phys. Rev. Lett. 94, 117803 (2005)] have demonstrated that these three settling behaviors can be achieved by control of the average particle concentration phi and inclination angle theta . This work presents a theory for determining the settling behavior in the Stokes regime by calculating the depth profile of… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
46
0

Year Published

2009
2009
2015
2015

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 28 publications
(46 citation statements)
references
References 13 publications
0
46
0
Order By: Relevance
“…(9) and (14) are henceforth referred to as the 'equilibrium equations'. As shown in the literature [9,10,14], the ODE solutions constitute a family of curves parametrized by the total volume of particles present within the fluid film, φ 0 (defined below). Before proceeding, since the equilibrium equations are explicitly independent of the axial flow direction and time, it is also convenient to remove their implicit dependence [present through h(x, t)], by rescaling the normal direction, z.…”
Section: Equilibrium Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…(9) and (14) are henceforth referred to as the 'equilibrium equations'. As shown in the literature [9,10,14], the ODE solutions constitute a family of curves parametrized by the total volume of particles present within the fluid film, φ 0 (defined below). Before proceeding, since the equilibrium equations are explicitly independent of the axial flow direction and time, it is also convenient to remove their implicit dependence [present through h(x, t)], by rescaling the normal direction, z.…”
Section: Equilibrium Modelmentioning
confidence: 99%
“…The solutions were found to approach the 'ridged' regime behavior but failed to capture the separation between the particle-free and particle-rich regions observed in the 'settled' regime. In the subsequent studies of Cook [14] and Cook et al [15], it was suggested that shear-induced migration phenomena are important and should be included in the dominant physics of the problem. The lubrication models derived in the above-mentioned studies assume that transport due to shear or settling occurs rapidly in the normal direction such that these processes depend solely on the axial flow direction and time.…”
Section: Introductionmentioning
confidence: 99%
“…One possibility of additional physics to include in this analysis is shear induced migration (e.g. [19,20]) which has recently been shown to give quantitatively accurate predictions of phase transitions between settling to the substrate and settling to contact line in constant flow-rate experiments [7]. It would also be interesting to incorporate a precursor into the physical experiments.…”
Section: Resultsmentioning
confidence: 99%
“…It is shown in [7] that this assumption can be improved to a distribution that is stationary in time which balances sedimentation and shear-induced migration. We refer to [7] for a precise discussion.…”
Section: A Lubrication Model For Particle-laden Flowmentioning
confidence: 99%
See 1 more Smart Citation